Simulation of the Effect of Correlated Packet Loss for sUAS Platforms Operating in Non-Line-of-Sight Indoor Environments - Edwin Meriaux; Jay Weitzen; Adam Norton (Drones, 2023)
The current state of the art in small Unmanned Aerial System (sUAS) testing and evaluation exists mainly in the realm of outdoor flight. Operating small flying sUAS in constrained indoor or subterranean environments places different constraints on their communication links (control links and camera/sensor links). Communication loss in these environments is much more severe due to the proximity of obstacles. This paper examines how correlated packet loss (burst errors) occurring on both the control and camera communication links affects the ability of pilots to fly and navigate small sUAS platforms in constrained Non-Line of Sight (NLOS) environments. A software test bench called AirSim, a UAV simulator, allows us to better understand the effects of correlated packet loss on flyability without damaging multiple sUAS units by flight testing. The simulation was designed to support the design of test methodologies for evaluating the robustness of the communication links and to understand performance without damaging flight tests. Throughout the simulations, it is observed how different levels of packet loss affect the pilot and the number of simulated crashes into the obstacles placed through space. The simulations modeled packet loss both on the video link and the control link to display how packet loss affects ability to pilot and control the sUAS. The utility of using a simulated environment rather than flight testing prevents damage to the fragile and expensive drones being used.